A rare case of multiple brain abscesses caused by Nocardia abscessus co-infection with tuberculous meningitis in an immunocompetent patient - Xiuri Wang; Lingyan Liang; Yunxiao Liang; Liuyang Hu (BMC Infectious Diseases)
Abstract Background Nocardial brain abscesses are extremely rare and predominantly affect immunocompromised patients, exhibiting a high overall mortality rate. Tuberculosis infections, although they can occur in immunocompetent individuals, are more prevalent in those with compromised immune systems. Tuberculous meningitis (TBM), the most severe manifestation of tuberculosis, is associated with a high fatality rate. Co-infection with both pathogens is unusual. To our knowledge, this is the first reported case of multiple brain abscesses caused by Nocardia abscessus (N. abscessus) in a young immunocompetent patient, complicated by tuberculous meningitis. Case presentation A 34-year-old male patient initially presented with a week-long history of headaches, predominantly localized in the bilateral frontal region. Additionally, the patient experienced fever, and due to the recurrence of these symptoms, he was admitted to the hospital. Chest computed tomography (CT) scans revealed bilateral pneumonia, and brain magnetic resonance imaging (MRI) strongly suggested the presence of multiple brain abscesses accompanied by meningitis. On the fourth day of hospitalization, the patient’s condition deteriorated, becoming lethargic with severe headaches. His body temperature spiked to 39.5 °C, and signs of elevated intracranial pressure emerged. Subsequently, he underwent neuro-navigation-assisted resection of deep lesions, ventriculostomy for external drainage, and drainage of abscesses. The next day, cerebrospinal fluid (CSF) Xpert MTB/RIF testing yielded positive results for multiple probes and the Mycobacterium tuberculosis (MTB) complex. Pus cultures and sequencing further confirmed an N. abscessus infection. Consequently, the patient was diagnosed with multiple brain abscesses caused by N. abscessus, complicated by tuberculous meningitis. We administered TMP-SMX, imipenem-cilastatin, and intravenous linezolid for the management of nocardial brain abscesses infections, while continuing decompressive ventricular drainage. For empiric treatment of tuberculous meningitis, the patient was started on isoniazid 600 mg/day via intravenous injection, rifampicin 600 mg/day orally, pyrazinamide 1500 mg/day (divided into three oral doses), ethambutol 750 mg/day orally, and dexamethasone at an initial dose of 0.4 mg/kg/day, with a planned gradual reduction starting one week later. Despite 10 days of treatment, the patient showed no significant clinical improvement in the infection, and hydrocephalus worsened. On the 16th day of admission, emergency external ventricular drain placement was performed, and intrathecal amikacin was administered to combat the nocardial brain abscesses. Unfortunately, by the 39th day of admission, the patient’s infection continued to progress, eventually succumbing to septic shock and resulting in death. Conclusions Nocardial brain abscesses are associated with a high mortality rate, especially among immunocompromised patients and those with multiple abscesses. Prompt diagnosis, aggressive surgical intervention, and sensitive antibiotic treatment offer the best prospects for curing nocardiosis. Tuberculous meningitis, the most lethal manifestation of Mycobacterium tuberculosis infection, often leads to severe outcomes primarily due to delayed diagnosis and treatment. The GeneXpert/RIF assay, an emerging diagnostic tool, provides a more sensitive and rapid means of detecting TBM. For patients with a high clinical suspicion of TBM, empirical anti-tuberculosis treatment should be initiated immediately. Timely and accurate management, coupled with continuous monitoring of the patient’s condition, is crucial for achieving a favorable prognosis. Clinical trial number Not applicable.